Knowledge, Attitudes, and Practices of Parents Regarding Malaria Chemoprevention for Children in ILORIN, KWARA State. - Ndeokwelu D.C; Ojo-Rowland O.T; Adeoti S.G; Yusuff Y.A; Oyun A.; Adebo A.O; Salawu O.V; Chinemelu C.E; Afolabi O.J; Dere A.A; Ibrahim S.A; Ozigis M.O; et al. (International Journal Of Family Medicine And Public Health, 2025)
Introduction: Malaria chemoprevention has been adopted in Nigeria as one of the preventive strategies aimed at reducing the burden of malaria, but the effectiveness of these interventions is intrinsically linked to the knowledge, attitudes, and practices of parents and caregivers regarding this malaria prevention strategy. This study aims to comprehensively assess the knowledge, attitudes, and practices of parents concerning this preventive method, thereby informing targeted interventions to improve uptake and adherence to malaria prevention strategies. Methods: A hospital-based, descriptive cross-sectional study design was employed using a convenient sampling technique to administer a pretested, semi-structured questionnaire to the sample population of caregivers of under 5 children at the outpatient department of the selected hospital. Results: The results indicate that although 57.2% of caregivers had heard of SMC, only 28.4% reported their child had taken it, revealing a disparity between awareness and actual uptake. Key barriers to SMC adoption included poverty, difficult access to healthcare services, and concerns over drug side effects. The study also revealed a significant relationship between caregivers’ knowledge of SMC and its uptake (p = 0.005). In addition, factors influencing caregivers’ decision to allow SMC treatment included perceived effectiveness, trust in healthcare providers, and accessibility of healthcare. Despite a generally positive attitude toward malaria prevention, existing knowledge gaps continue to hinder the effective implementation of preventive measures. Conclusion: The study concluded that enhancing health education and awareness, improving healthcare service accessibility, and addressing socioeconomic challenges are vital 1. Ajayi, M.Y., Emeto, D.C. Awareness and acceptability of malaria vaccine among caregivers of under-5 children in Northern Nigeria. Malar J 22, 329 (2023). https://doi.org/10.1186/s12936-023-04768-z 2. Ogbulafor, N., Uhomoibhi, P., Shekarau, E., Nikau, J., Okoronkwo, C., Fanou, N. M. L., Mbaye, I. M., Ndiaye, J. L., Tchouatieu, A. M., PokuAwuku, A., Merle, C., Scott, S., Milligan, P., Ali, A., Yusuf, H. E., Oguche, S., & Dahiru, T. (2023). Facilitators and barriers to seasonal malaria chemoprevention (SMC) uptake in Nigeria: a qualitative approach. Malaria journal, 22(1), 120. https://doi.org/10.1186/s12936-023- 04547-w 3. Ahluwalia, J., Brooks, S.K., Weinman, J. et al. A systematic review of factors affecting adherence to malaria chemoprophylaxis amongst travellers from non-endemic countries. Malar J 19, 16 (2020). https:// doi.org/10.1186/s12936-020-3104-4 4. Cairns M, Ceesay SJ, Sagara I, Zongo I, Kessely H, Gamougam K, Diallo A, Ogboi JS, Moroso D, Van Hulle S, Eloike T, Snell P, Scott S, Merle C, Bojang K, Ouedraogo JB, Dicko A, Ndiaye JL, Milligan P. Effectiveness of seasonal malaria chemoprevention (SMC) treatments when SMC is implemented at scale: Case-control studies in 5 countries. PLoS Med. 2021 Sep 8;18(9):e1003727 5. Koko, D.C., Maazou, A., Jackou, H. et al. Analysis of attitudes and practices influencing adherence to seasonal malaria chemoprevention in children under 5 years of age in the Dosso Region of Niger. Malar J 21, 375 (2022). https://doi.org/10.1186/s12936-022-04407-z 6. Olawumi, H. O., Fadeyi, A., Babatunde, S. K., Akanbi, A. A., 2nd, Babatunde, A. S., Sani, M. A., & Aderibigbe, S. A. (2015). Malaria Parasitaemia among Blood Donors in Ilorin, Nigeria. African journal of infectious diseases, 9(1), 10–13. https://doi.org/10.4314/ajid.v9i1.3 7. Adedoja, A., Babatunde, S. K., Tijani, B. D., Akanbi, A. A., & II, O. O. (2019). Usefulness of Polymerase Chain Reaction in the diagnosis of asymptomatic malaria among school age children in Ilorin, Nigeria. Pan African Journal of Life Sciences, 1, 39-45. 8. Kio, J. O., Agbede, C. O., Olayinka, F. E., Omeonu, P. E., & Dire-Arimoyo, Y. (2016). Knowledge, attitudes, and practices of mothers of under-five regarding prevention of malaria in children: Evidence from Ogun State, Nigeria. IOSR Journal of Humanities and Social Science (IOSR-JHSS), 21(8), 1-7. https://doi.org/10.9790/0837-2108080107 9. Singh R, Godson II, Singh S, Singh RB, Isyaku NT, Ebere UV. High prevalence of asymptomatic malaria in apparently healthy schoolchildren in Aliero, Kebbi state, Nigeria. J Vector Borne Dis. 2014 Jun;51(2):128-32 10. Kimbi HK, Nkesa SB, Ndamukong-Nyanga JL, Sumbele IU, Atashili J, Atanga MB. Knowledge and perceptions towards malaria prevention among vulnerable groups in the Buea Health District, Cameroon. BMC Public Health. 2014 Aug 27;14:883 11. de Sousa Pinto, L., Arroz, J.A.H., Martins, M.d.R.O. et al. Malaria prevention knowledge, attitudes, and practices in Zambezia Province, Mozambique. Malar J 20, 293 (2021). https://doi.org/10.1186/ s12936-021-03825-9 12. Babalola, DA, Olarewaju M, Omeonu PE, Adefelu A O and Okeowo, R, Assessing the adoption of Roll Back Malaria Programme (RBMP) among women farmers in Ikorodu Local government area of Lagos state. Canadian Journal of Pure and Applied Science. 7 ( 2), 2013, 2375- 2379 13. Manana, P.N., Kuonza, L., Musekiwa, A. et al. Knowledge, attitudes and practices on malaria transmission in Mamfene, KwaZulu-Natal Province, South Africa 2015. BMC Public Health 18, 41 (2018). https:// doi.org/10.1186/s12889-017-4583-2 14. Addis D, Gebeyehu Wondmeneh T. Assessment of malaria prevention knowledge, attitude, and practice and associated factors among households living in rural malaria-endemic areas in the Afar Pastoral Region of Ethiopia. Front Public Health. 2023 15. Diarra, Y. et al. (2025) ‘Caregiver acceptability of seasonal malaria chemoprevention in two districts in the Upper West region, Ghana: a cross-sectional study’, Malaria journal, 24(1), p. 14. Available at: https://doi.org/10.1186/s12936-024-05169-6 16. Ibinaiye, T. et al. (2023) ‘Predictors of caregiver adherence to administration of amodiaquine during delivery of seasonal malaria chemoprevention in Nigeria, Burkina Faso, Chad, and Togo’, Malaria Journal, 22(1). Available at: https://doi.org/10.1186/s12936-023- 04576-5. 17. Dicko, I., Coulibaly, Y.I., Sangare, M., Sarfo, B. and Nortey, P.A. (2020) ‘Non-compliance to mass drug administration associated with the low perception of the community members about their susceptibility to lymphatic filariasis in Ankobra, Ghana’, Infectious Disorders - Drug Targets, 20, pp. 167–174. 18. Antwi, G.D., Bates, L.A., King, R., Mahama, P.R., Tagbor, H., Cairns, M. et al. (2016) ‘Facilitators and barriers to uptake of an extended seasonal malaria chemoprevention programme in Ghana: a qualitative study of caregivers and community health workers’, PLoS ONE, 11, e0166951. 19. Ba, E.H., Pitt, C., Dial, Y., Faye, S.L., Cairns, M., Faye, E. et al. (2018) ‘Implementation, coverage and equity of large-scale door-to-door delivery of seasonal malaria chemoprevention (SMC) to children under 10 in Senegal’, Scientific Reports, 8, p. 5489. 20. Ngasala, B. et al. (2023) ‘Malaria knowledge, attitude, and practice among communities involved in a seasonal malaria chemoprevention study in Nanyumbu and Masasi districts, Tanzania’, Frontiers in Public Health [Preprint]. Available at: https://doi.org/10.3389/ fpubh.2023.976354.